2012
DOI: 10.1002/art.33423
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of arthritis by macrophage depletion and immunomodulation: Testing an apoptosis‐mediated therapy in a humanized death receptor mouse model

Abstract: Objective To determine the therapeutic efficacy and immunomodulatory effect of an anti-human death receptor 5 (DR5) antibody, TRA-8, in eliminating macrophage subsets in a collagen II-induced arthritis (CIA) mouse model. Methods A chimeric human/mouse (hu/mo) DR5 transgenic (Tg) mouse, under the regulation of the mouse 3-kb promoter and a Floxed-STOP cassette, was generated and crossed with an ubiquitous Cre (Ubc.Cre) and a lysozyme M Cre (LysM.Cre) Tg mouse to achieve inducible- or macrophage-specific expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 48 publications
4
55
0
Order By: Relevance
“…Targeting molecules that promote macrophage proliferation, accumulation or activation (eg, CSF-1, granulocytemacrophage colony-stimulating factor, TNF-a, IL-1b, and IL-6) [33][34][35][36][37][38][39][40] suppresses CIA in mice. As has been reported using antibodymediated macrophage depletion, 41 we found that macrophage depletion by systemic clodronate administration resulted in amelioration of CIA to an extent analogous to what was observed with uPAdeficient mice (data not shown). Local macrophage depletion by intraarticular clodronate injections has shown some benefit in rheumatoid arthritis, 42 and macrophage depletion is still explored as a therapeutic option within inflammatory diseases.…”
Section: Discussionsupporting
confidence: 84%
“…Targeting molecules that promote macrophage proliferation, accumulation or activation (eg, CSF-1, granulocytemacrophage colony-stimulating factor, TNF-a, IL-1b, and IL-6) [33][34][35][36][37][38][39][40] suppresses CIA in mice. As has been reported using antibodymediated macrophage depletion, 41 we found that macrophage depletion by systemic clodronate administration resulted in amelioration of CIA to an extent analogous to what was observed with uPAdeficient mice (data not shown). Local macrophage depletion by intraarticular clodronate injections has shown some benefit in rheumatoid arthritis, 42 and macrophage depletion is still explored as a therapeutic option within inflammatory diseases.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with this notion, it was reported that macrophage depletion results in the suppression of CIA associated with downregulation of these inflammatory mediators (46). Thus, these observations suggest that IL-1R2 regulates the development of arthritis by suppressing IL-1 activity on macrophages.…”
Section: Discussionsupporting
confidence: 75%
“…Although TRAIL/TRAILR system is generally considered to be a component of the cell anti-tumorigenic activity, its physiopathological role is broader than originally thought (Di Pietro & Zauli 2004). In particular, the ability of TRAIL to suppress inflammatory reactions has been demonstrated in a variety of studies (Li et al 2012, Marcuzzi et al 2012, Keuper et al 2013, Secchiero et al 2013, Walczak 2013. The second major finding of our study was that recombinant TRAIL, used at concentrations comparable to those found in seminal plasma (10 ng/ml), significantly increased the overall survival of capacitated spermatozoa.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, the presence of TRAIL in seminal plasma has never been evaluated. It should also be taken into consideration that a growing number of studies from different groups of investigators have shown that TRAIL displays anti-inflammatory activity (Li et al 2012, Marcuzzi et al 2012, Keuper et al 2013, Secchiero et al 2013, Walczak 2013. On these bases, the aim of our present study was i) to analyze the presence and the levels of soluble TRAIL in the seminal samples and the surface expression of TRAIL receptors in the sperm cellular fraction and ii) to evaluate the potential biological activity of soluble TRAIL, by assessing the in vitro response of spermatozoa in terms of vitality/survival and motility upon exposure to recombinant TRAIL.…”
Section: Introductionmentioning
confidence: 99%